Small Microplastics: A yet Unknown Threat in the Svalbard (Norway) Region - Caruso, Gabriella; Iannilli, Valentina; Vitale, Giulia; Vardè, Massimiliano; Oliverio, Marco; Bogialli, Sara; Litti, Lucio; Setini, Andrea; Rosso, Beatrice; Corami, Fabiana (Journal of Marine Science and Engineering, 2023)
The Arctic Ocean is undergoing several transformations because of global climate change. Small microplastics (SMPs) or nanoplastics (NPs) carried by marine aerosols may settle in the land ice and be released to the waters, produced following its melting. As sea ice extent reduces and shipping and fishing activities increase, microplastics (MPs) may enter the region following ocean and maritime transports, with implications on Arctic biota, human health, and socioeconomic issues related to the exploitation of marine resources. First analyses on amphipods collected in Ny-Ålesund confirmed the presence of SMPs. Nevertheless, the threat posed by SMPs/NPs to polar biota and regional human health is not fully understood. This article addresses this issue and the need for organisms as potential bioindicators of plastic pollution, which is currently being carried out in the Svalbard region under the framework of the MICROTRACER project funded by the Italian Arctic Research Program (PRA, Call 2021). The outputs of this research are expected to contribute to deepening the current knowledge of SMPs in Svalbard, providing new insights on their occurrence, distribution, and transfer through the marine trophic web, to realize effective control and regulatory framework measures to implement an integrated multidisciplinary approach for monitoring and to reduce MPs pollution in this fragile polar environment.